Microalgal biotechnology : recent advances, market potential, and sustainability - Shekh, Ajam; Schenk, Peer (Royal Society of Chemistry, 2021)
Microalgal Biotechnology consolidates the latest research in the field together with a look at market potential and policy considerations.